Untwinned semipolar (101̅3) AlxGa1-xN layers grown on m-plane sapphire. (8th November 2019) - Dinh, Duc V; Hu, Nan; Amano, Hiroshi; Honda, Yoshio; Pristovsek, Markus
Abstract: Heteroepitaxial growth of untwinned mono-crystalline semipolar (101̅3) Al x Ga 1 − x N layers on (101̅3) AlN template was investigated by metalorganic vapour phase epitaxy. The templates were initially deposited on (101̅0) m -plane sapphire substrates by directional sputtering. Different Al/Ga ratios in gas phase were used to adjust the AlN mole fraction over the entire range of composition. All the layers show a triclinic distortion in the wurtzite unit cell due to anisotropic in-plane strain. The AlN mole fraction of the (101̅3) layers and c -plane co-loaded layers estimated by x-ray diffraction is comparable. This is consistent both with their comparable effective bandgap energy estimated from optical transmission measurements and their near band-edge emission energy obtained from room-temperature photoluminescence. The dependence of the bandgap and near band-edge emission energies on the AlN mole fraction indicates a bowing parameter of 0.9 eV.